Renal outcome in multiple myeloma patients with cast nephropathy: a retrospective analysis of potential predictive values on clinical and renal outcome - Lina Z. Rüsing; Nicolas Kozakowski; Georg Jeryczynski; Lea Vospernik; Julia Riedl; Thomas Reiter; Heinz Gisslinger; Hermine Agis; Maria-Theresa Krauth (Hematology)
Objective Cast nephropathy (CN) is the leading cause of acute kidney injury (AKI) in multiple myeloma (MM). Since it is sparsely documented why some patients with CN do achieve a renal response while others do not, we describe a single-center cohort of patients with multiple myeloma and biopsy-confirmed CN to evaluate potential markers of renal response.Methods The data was collected as a retrospective, single-center analysis of CN-patients treated at the Medical University Vienna between 01/01/2004 and 01/01/2022. Baseline parameters and clinical outcome was compared between renal responders and non-responders.Results Among 28 patients with CN, n = 23 were assessed for renal response (14 responders; 9 non-responders). Renal responders were younger (median age: 61 years; 77 years, p = 0.039), showed higher overall survival (153months; 58months, p = 0.044) and achieved hematologic response (≥PR) to first-line therapy (p = 0.029), and complete hematologic response (CR) at any time (p = 0.025) significantly more often. Further, we could show that rapid initiation of anti-myeloma therapy after initial presentation correlated significantly with renal response (median 9 days; 27 days, p = 0.016). Analyses of kidney biopsy specimens revealed that patients with a high IF/TA score showed end stage renal disease (dialysis ≥ 3 months) significantly more often (p = <0.001).Discussion In summary, our data suggests, that a rapid start with systemic hematologic treatment in patients with MM and CN is crucial and achieving an early hematologic response is important for renal recovery. Moreover, achieving a deep hematologic response and subsequent renal recovery improves clinical outcome as reflected by an overall survival benefit.